2009
DOI: 10.5194/acp-9-1621-2009
|View full text |Cite
|
Sign up to set email alerts
|

The Tropical Tropopause Layer 1960–2100

Abstract: Abstract. The representation of the Tropical Tropopause Layer (TTL) in 13 different Chemistry Climate Models (CCMs) designed to represent the stratosphere is analyzed. Simulations for 1960 and 1980 -2100 are analyzed. Simulations for 1960 are compared to reanalysis model output. CCMs are able to reproduce the basic structure of the TTL. There is a large (10 K) spread in annual mean tropical cold point tropopause temperatures. CCMs are able to reproduce historical trends in tropopause pressure obtained from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 55 publications
5
87
0
Order By: Relevance
“…A lifted and warmer tropopause under higher SSTs suggests that warming of the troposphere due to SST increases dominates the tropopause temperature changes. This result is consistent with Gettelman et al (2009), who showed that the tropopause is projected to be lifted and warmed in the future based on different CCM simulations.…”
Section: Effects Of Sst Changes On the Bdc And Tropopausesupporting
confidence: 81%
“…A lifted and warmer tropopause under higher SSTs suggests that warming of the troposphere due to SST increases dominates the tropopause temperature changes. This result is consistent with Gettelman et al (2009), who showed that the tropopause is projected to be lifted and warmed in the future based on different CCM simulations.…”
Section: Effects Of Sst Changes On the Bdc And Tropopausesupporting
confidence: 81%
“…For the remaining models, models with low grades for the tropical temperature tend to have low grades for the water vapor diagnostic, and there is a much higher correlation (0.88). A higher correlation is found between the tropical cold point and 100 hPa water vapor correlation (Gettelman et al, 2008), but the above two models are still anomalous. The sensitivity of the correlations to results of two models illustrates that care should be taken interpreting these correlations.…”
Section: Relationships Among Diagnosticsmentioning
confidence: 96%
“…This might indicate a climate change signal, with possible important impacts on stratospheric climate: e.g. tropical tropopause temperatures dominate the amount of water vapour entering the stratosphere (Dessler et al, 2013(Dessler et al, , 2014Gettelman et al, 2009;Randel and Jensen, 2013). So far a long-term cooling in the lower stratosphere has been reported from the 1970s to 2000, although there are large differences between different data sets (Randel et al, 2009;Wang et al, 2012;Fueglistaler et al, 2013).…”
Section: W Wang Et Al: Contributions To Recent Ttl Variabilitymentioning
confidence: 99%